PERAN AKAL DALAM MEMAHAMI PENGETAHUAN LADUNI (TELAAH KITAB RISALAH AL-LADUNIYYAH AL GHAZALI) - Azizatun Nisa (Refleksi: Jurnal Filsafat dan Pemikiran Keislaman, 2019)
This research is a qualitative research. The aim is finding out the role of reason in understanding laduni knowledge. In this case laduni knowledge is the same as intuition. The relationship of reason and intuition which is essentially always in an interactive condition, first seeing the types of knowledge that can be captured by humans. According to al-Ghazali there are four kinds of levels of existence (being). First. The metaphysical form, according to him, is summarized in the Mahfudh letter. Second, empirical forms in the concrete world (alam syahadah). Third, imaginary (imaginative), and fourth, rational form (al-ma’qulat). The relationship of reason and intuition, al-Ghazali made a parable of people who gained knowledge with reason likened to a child and those who obtained knowledge with intuition were likened to (al-mumayyiz). The parable above implies the existence of a level between the two and does not mean there is a separation between each. If this is related to the theory of the human ratio (al- nafs al-natiqoh) after being able to capture a priori or dharuriyyat knowledge, in turn it shows two abilities, namely, the ability to produce knowledge through understanding (through) feeling . The first is creative-methodical-systematic, while the second is creative-non-systematic-systematic. Thus, it is clear that the nature of both knowledge comes from the same source as the derivative of the soul and therefore both are contained in human intellectuality.